Managing Coexisting Pulmonary Tuberculosis and Type 2 Diabetes Mellitus in a 52-Year-Old Woman: A Family Medicine Approach - Jamilah, Faizatul; Rusnianah, Farida; Noor Pratami, Gia (Jurnal Ilmu Kedokteran Keluarga, 2026)
Tuberculosis (TB) and Type 2 Diabetes Mellitus (T2DM) are chronic conditions that often coexist and mutually worsen clinicaloutcomes. We report a 52-year-old widowed female, a beverage vendor, with a three-month history of productive cough, weightloss, and night sweats, and a 25-year history of poorly controlled T2DM. Random blood glucose ranged from 200–539 mg/dL, andGeneXpert MTB/RIF confirmed pulmonary TB. Psychosocial assessment revealed strong family support, though SCREEMidentified limitations in social, economic, and educational domains. Environmental risks included overcrowded housing, poorventilation, and daily smoke exposure. Management consisted of first-line anti-tuberculosis therapy (RHZE), oral hypoglycemicagents (metformin, glibenclamide), lifestyle counseling, sleep hygiene, and environmental modification, with her son serving as atreatment supporter. Two home visits reinforced adherence and lifestyle changes, though glycemic control remained suboptimal.This case demonstrates that a comprehensive family medicine approach integrating biomedical treatment, family engagement, andcontextual lifestyle interventions is essential for effective management of TB-DM comorbidity.